Cervical ectopic pregnancy: a rare case report - Verma, Indu; Chugh, Charvi; Santpur, Unmesh; Pundhir, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Cervical ectopic pregnancy is rare condition which occurs in less than 1% of all ectopic pregnancies. Early diagnosis is a key to successful management; delayed diagnosis can lead to significant morbidity and fertility loss of the mother. We present a case of woman who presented with vaginal bleeding and lower abdominal pain for 3 days following amenorrhea of 3 ½ months. Ultrasound examination done outside was suggestive of left tubal ectopic pregnancy whereas scan done at our hospital indicated either uterine rupture within intraperitoneal sac or a cervical ectopic pregnancy. She was taken up for laparotomy and hysterectomy since she was bleeding profusely, and it was lifesaving.